Exploring the multidimensional relationships between educational situation perception, teacher support, online learning engagement, and academic self-efficacy in technology-based language learning - Pan, Xiaoquan (Frontiers in Psychology, 2022)
The study explored the multidimensional relationships between educational situation perception, teacher support, online learning engagement and academic self-efficacy in technology-based language learning in a sample of Chinese undergraduate students, and meanwhile examined the mediating effects of academic self-efficacy and teacher support. A total of 392 (126 male and 266 female) Chinese university students reported on their perceived educational situation, teacher support, online learning engagement, and academic self-efficacy. Results showed that educational situation perception was significantly and positively associated with teacher support, online learning engagement and academic self-efficacy; teacher support and academic self-efficacy was positively correlated with online learning engagement. More importantly, academic self-efficacy as well as teacher support mediated the relationship between educational situation perception and online learning engagement. These findings extended previous research by considering both the external factors (i.e., educational situation; teacher support) and the internal factors (i.e., academic self-efficacy) of influencing students’ online learning engagement in technology-based language learning, thereby contributing to enhancing our understanding of the joint drive of the inherent and extrinsic power mechanisms. This study highlighted the following aspects: (1) strengthening the consideration of the key elements of the educational situation; (2) clarifying the pivotal position of intelligent technology in educational situations; and (3) emphasizing the reconstruction of intelligence teaching ecology driven by learning activities. Besides, this study indicated the significance of elevating teachers’ awareness, willingness and capacity of the substantial supports in enhancing students’ online learning engagement and would inform that the future research on the connotation and ways of teacher support should be responding to technology-based learning environments.